POLITIK HUKUM PEMERINTAH DAERAH DALAM PENYUSUNAN ANGGARAN PENDAPATAN DAN BELANJA DAERAH (APBD) DALAM PERSPEKTIF OTONOMI DAERAH DAN DEMOKRASI - Mointi, Rahayu; Tumuhulawa, Arifin; Kadir, Yusrianto (At-Tanwir Law Review, 2024)
This study aims to examine and analyze the Misuse of Village Fund Management in the Criminal Law Perspective and analyze Efforts to This study aims to analyze the Legal Politics of Local Government in the Preparation of Regional Expenditure Revenue in the Perspective of Regional Autonomy and Democracy and analyze the Urgency of Strategic Programs in the Preparation of Regional Expenditure Revenue and Determination to Realize an Independent and Prosperous Region. The research method used is normative research, namely, legal research carried out using literature review and review of legislation. The results showed that  the Urgency of Strategic Programs in the Preparation of Regional Expenditure Revenue Budgets and Determination to Realize an Independent and Prosperous Region, namely Regional Governments in developing their regions, to prosper their communities by improving, accelerating community services, empowering and community participation as well as increasing regional competitiveness by taking into account the principles of democracy, equity, justice,  the privileges and particularities of a region in the Unitary State system of the Republic of Indonesia, which is a reference for local governments in planning budgeting.